GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 52293 species occurrences available in GBIF matching the query: TaxonKey: Terebellidae Malmgren, 1867. The dataset includes 52293 records from 178 constituent datasets: 8 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 370 records from Annelida collection of National Museum of Nature and Science. 13 records from Gwaii Haanas Marine Plants (OBIS Canada). 12 records from South American Antarctic Marine Biodiversity Literature. 50 records from Paleobiology Database. 4 records from Tartu University, palaeontology collections. 34 records from Polish Arctic Marine Programme (EurOBIS). 1 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 261 records from SO-Polylist. 9 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82 (Australian Antarctic Data Centre). 7 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 1775 records from NBI. 4 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 24 records from iNaturalist research-grade observations. 143 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE241. 121 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 119 records from Natural Geography In Shore Areas (NaGISA) Dataset. 124 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE236. 430 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 30 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 1 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 4363 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 6 records from Antarctic Marine Species Sequence Data. 246 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 417 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 161 records from Marine species distributions in Irish coastal waters. 24 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 675 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 106 records from Bishop Museum Natural Sciences Data. 2 records from Marine specimens of Misaki Marine Biological Station, School of Science, University of Tokyo. 5 records from Museum of Zoology, University of Navarra. 19 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 24 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups. . 1 records from Ireland's BioBlitz 2012. 22 records from MfN - Fossil vertebrates III. 6 records from MNA - Sezione di Genova - (Marine Biological Samples). 56 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 3 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2007. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 358 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 473 records from Lund Museum of Zoology (MZLU). 37 records from Coleção de Polychaeta do Museu Nacional. 3 records from (Table 2a) Abundance of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 24 records from UMZC Zoological Specimens. 7 records from N3 data of Kiel bay (EurOBIS). 1 records from NCOS1959_Mollusca (OBIS China). 24 records from COMARGIS: Information System on Continental Margin Ecosystems. 45 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 1 records from MICROBIS database. 39 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 38 records from Marine invertabrate(ECHINODERMATA) specimen database of Osaka Museum of Natural History. 557 records from Biogeography Scheldt Estuary (EurOBIS). 1507 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 3 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 23 records from Cross Sands broadscale survey 1998 (EurOBIS). 3430 records from Marine Conservation Society - Seasearch Marine Surveys . 20 records from naturgucker. 43 records from Histroical benthic dredge samples from the southern baltic and the North Sea (EurOBIS). 43 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 9 records from UAM Invertebrate Collection (Arctos). 1102 records from Invertebrates (GBIF-SE:SMNH). 9 records from Arctic soft-sediment macrobenthos (EurOBIS). 5 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 7 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 153 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE233. 9 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 27 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 11 records from Bishop Museum Data (OBIS distribution) (USOBIS). 2 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 95 records from IndOBIS, Indian Ocean Node of OBIS. 1 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 372 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 16 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 5 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 646 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 36 records from Benthic fauna in the Pechora Sea (EurOBIS). 18 records from Epi-endofauna abundance in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 3 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 29 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 1098 records from Museum Victoria provider for OZCAM. 1848 records from EPA'S EMAP Database. 4 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 2 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 3 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 73 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE218. 16 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 41 records from Sponges of Rathlin Island. 306 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from ChEssBase (CoML). 2 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 166 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 74 records from Abundance of Lanice in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 1708 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN. . 1 records from Diveboard - Scuba diving citizen science observations. 10 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 495 records from invertebratezoology. 94 records from Collection Polychaeta - ZIM Hamburg. 524 records from Collection Polychaeta SMF. 1 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 531 records from Zoology (Museum of Evolution - Uppsala). 1 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 561 records from Macrobel: Long term trends in the macrobenthos of the Belgian Continental Shelf (EurOBIS). 1255 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 2095 records from Geographically tagged INSDC sequences. 132 records from Atlas Nacional de Anélidos Poliquetos de México (ICMyL-DF, UNAM). 15 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Naturhistorisches Museum Mainz, Paleontological Collection. 556 records from DINA. 132 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 10 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 1 records from NCSM Invertebrate Paleontology Collection. 6 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 2 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 16 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 6 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 5 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 2 records from Artenvielfalt der Nordsee - Sylt. 420 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 44 records from Atlantic Reference Centre (OBIS Canada). 122 records from Arctic Ocean Diversity. 17 records from SeamountsOnline (seamount biota) (CoML). 43 records from NOAA HML Tidal Creek Database. 470 records from MedOBIS (EurOBIS). 16 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 87 records from Collection Polychaeta - ZSRO. 1 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 6 records from IG TUT paleontology. 141 records from Colección de Anélidos Poliquetos del Pacífico Mexicano (UANL). 1 records from Wangerooge. 605 records from Collection Vermes - ZMB. 50 records from BioFokus. 11 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 129 records from NCOS (OBIS China). 5819 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 389 records from BioMar - LIFE project. 7 records from SOMBASE. 1 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (79° N section). 14 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 233 records from Natural England - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 170 records from Gwaii Haanas Invertebrates (OBIS Canada). 125 records from Rådgivende Biologer. 3 records from MarBEF Publication Series data (EurOBIS). 447 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 23 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 14 records from Bay of Fundy Species List (OBIS Canada). 377 records from CAS Invertebrate Zoology (IZ). 119 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 1 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 979 records from Artdata. 3 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 24 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 6 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 2109 records from Australian Museum provider for OZCAM. 6 records from Collection Paleontology - GPIT. 2 records from Artenvielfalt der Nordsee - Helgoland. 21 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 6 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 6 records from NODC WOD01 Plankton Database. 2 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 3 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 7 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 8 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 14 records from ECatSym: Electronic World Catalog of Symphyta. 18 records from CU Invertebrate Paleontology. 5327 records from NMNH occurrence DwC-A. 374 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 13 records from BioMar (EurOBIS). 1150 records from Natural History Museum (London) Collection Specimens. 1 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 217 records from Museum of Comparative Zoology, Harvard University. 1074 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 3 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 112 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 36 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 20 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 137 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133.
Keywords: GBIF; biodiversity; species occurrences